A two-phase genetic algorithm to solve variants of the batch sequencing problem - Carsten Jordan (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1995)
We introduce the batch sequencing problem with item and batch availability for the single machine and two machine flow-shop case. We propose a genetic algorithm which solves all variants through a decomposition of the problem into a Phase I-Batching and a Phase II-Scheduling decision. The batch sequencing problem is closely related to the discrete lotsizing and scheduling problem (DLSP). Computational experience shows that our algorithm favourably compares with procedures for the DLSP. – – Wir betrachten das Batch Sequencing Problem mit geschlossener und offener Produktweitergabe fuer den Ein-Maschinen- und Zwei-Maschinen Flow-Shop Fall. Ein genetischer Algorithmus loest alle Varianten durch Dekomposition der Loesung in eine Phase I-Batching und eine Phase II-Scheduling Entscheidung. Das Batch Sequencing Problem haengt eng zusammen mit dem Discrete Lotsizing and Scheduling Problem (DLSP). Rechenergebnisse zeigen, dass der genetische Algorithmus leistungsfaehiger ist als die DLSP Loesungsverfahren.
Keywords: 650; Produktionssteuerung; Theorie